2019
DOI: 10.1039/c9cp02996f
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer thickness determines the alignment of model polyproline helices in lipid membranes

Abstract: We describe the design and experimental observation of an entirely new transmembrane helical peptide motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Although it is hydrophobic in nature, the halogen introduces some interesting physico-chemical features not normally associated with this property, such as allowing for the possibility of F···H–N hydrogen bond formation. This is confirmed by through-space coupling in NMR studies [ 17 , 18 ].…”
Section: The Structural and Physico-chemical Effects Of Halogen Atoms In Polypeptidesmentioning
confidence: 54%
See 1 more Smart Citation
“…Although it is hydrophobic in nature, the halogen introduces some interesting physico-chemical features not normally associated with this property, such as allowing for the possibility of F···H–N hydrogen bond formation. This is confirmed by through-space coupling in NMR studies [ 17 , 18 ].…”
Section: The Structural and Physico-chemical Effects Of Halogen Atoms In Polypeptidesmentioning
confidence: 54%
“…Furthermore, halogenation, such tryptophan bromination, resulted to be useful to optimize [ 221 ] the characteristics of bioactive molecules with pharmaceutical activity, as shown for products from marine organisms. Fluorine is efficaciously used as an internal probe for F 19 -NMR studies of peptide and protein structure-activity relationships (SAR), especially in interaction with biological membranes [ 18 , 222 ]. SAR studies have also revealed a correlation between the enhanced hydrophobicity resulting from halogenation and the antimicrobial activity of AMPs and their pep-tidomimetics.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…The answer is ‘yes’. Very recently we demonstrated experimentally that the polyproline-II helix can be integrated to the membrane and adopt a defined transmembrane alignment [62,63]. A successive study showed that the collagen helix, a fold made out of assembled polyproline-II helices, has no fundamental limitations to do so as well [64].…”
Section: The Proline Worldmentioning
confidence: 99%
“…The presence of these groups adjacent to the proline structure helps to modulate the conformational landscape of the parent amino acid, and this effectively alters the folding of the peptide chain when an analogue is included in it as a residue [49,50]. The presence of a fluorine-rich group in the structure is also beneficial for the NMR studies based on the detection of the 19 F nucleus [51][52][53]. Limited attention has been given to the polarity effects in the proline analogues though.…”
Section: Introductionmentioning
confidence: 99%